Water Conveyance Efficiency and Quality with Water Filtration Plant Cucumber son Fish Farming Technology Based Akuaponik carp - Haryanto Rohman Siregar; Sumono Sumono; Saipul Bahri Daulay; Edi Susanto (Universitas Sumatera Utara, 2013)
The basic principles used in the system is are circulation akuaponik, there use of water that has been used in the cultivation of carp, through a combination of akuaponik and hydroponics. This study aims to determine the water conveyance efficiency of water in plants, knowing the degree of acidity (pH), dissolved oxygen (DO) of water, ammonia (NH3) and the temperature in the process of raising fish and cucumber plants, and perform economi analysis methods applied akuaponik. The results of this study showed average water conveyance efficiency on full half coal pan 100 % end on full coal pan 79,61 %, well as a solid stocking of carp weighing 50ekor/m2 reached 147-150 grams per fish of initial weight 80-110 grams per cow within 3 months. Water quality pH, DO, NH3, and temperature shows the water quality meets there quirements of carp culture. Break even point production for fish 460,1 ton/years and 403,1 ton/years for cucumber plants. Keywords: water conveyance efficiency, water quality, plant cucumbers, akuaponik, and carp.